2020
DOI: 10.1126/sciadv.aaz9488
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and microstructural changes in cosmonauts’ brains after long-duration spaceflight

Abstract: Long-duration spaceflight causes widespread physiological changes, although its effect on brain structure remains poorly understood. In this work, we acquired diffusion magnetic resonance imaging to investigate alterations of white matter (WM), gray matter (GM), and cerebrospinal fluid (CSF) compositions in each voxel, before, shortly after, and 7 months after long-duration spaceflight. We found increased WM in the cerebellum after spaceflight, providing the first clear evidence of sensorimotor neuroplasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
77
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 45 publications
(96 reference statements)
11
77
0
2
Order By: Relevance
“…They demonstrated that the vast majority of GM changes were due to volume shifts; these GM changes were largely reversed on 7-month follow up, in agreement with previous studies 25 . Interestingly, by their method, a net gain of GM tissue was noted in the basal ganglia, an area involved in voluntary movement 25 . In addition, Jillings et al noted increased WM volume in the cerebellum, corticospinal tract and primary motor cortex in cosmonauts immediately following spaceflight, which were partially resolved on 7 month follow-up scan.…”
Section: Changes To Cerebrospinal Fluid Circulation After Spaceflightsupporting
confidence: 89%
See 2 more Smart Citations
“…They demonstrated that the vast majority of GM changes were due to volume shifts; these GM changes were largely reversed on 7-month follow up, in agreement with previous studies 25 . Interestingly, by their method, a net gain of GM tissue was noted in the basal ganglia, an area involved in voluntary movement 25 . In addition, Jillings et al noted increased WM volume in the cerebellum, corticospinal tract and primary motor cortex in cosmonauts immediately following spaceflight, which were partially resolved on 7 month follow-up scan.…”
Section: Changes To Cerebrospinal Fluid Circulation After Spaceflightsupporting
confidence: 89%
“…In addition, Jillings et al noted increased WM volume in the cerebellum, corticospinal tract and primary motor cortex in cosmonauts immediately following spaceflight, which were partially resolved on 7 month follow-up scan. Taken together, these results may suggest that spaceflight induces WM volume increases in the motor and coordination regions of the brain, which partially resolves upon return to earth 25 . Several studies have also utilized diffusion-weighted MRI to examine the microstructure of WM by fractional anisotropy.…”
Section: Changes To Cerebrospinal Fluid Circulation After Spaceflightmentioning
confidence: 72%
See 1 more Smart Citation
“…These studies have also provided evidence for vestibular cortex reorganization and multisensory reweighting following spaceflight. The authors did not report if the cosmonauts who participated in these studies developed SANS during spaceflight, though it has been reported that cosmonauts do not develop SANS perhaps due to differences in in-flight countermeasures used by astronauts and cosmonauts 61 .…”
Section: Subgroup Differences In Longitudinal Changes In Functional Connectivitymentioning
confidence: 98%
“…Microgravity induces a physical body unloading and a headward fluid shift ( Marshall-Goebel et al, 2019b ). Structural brain changes observed in astronauts after return from International Space Station (ISS) missions have included an upward shift of the brain ( Roberts et al, 2017 ; Lee et al, 2019 ; Roberts et al, 2019 ), changes in gray matter volume ( Koppelmans et al, 2016 ), increased white matter in the cerebellum ( Jillings et al, 2020 ), and cerebrospinal fluid volume increases in the third and lateral ventricles ( Alperin et al, 2017 ; Roberts et al, 2017 ; Van Ombergen et al, 2019 ; Jillings et al, 2020 ; Kramer et al, 2020 ). The functional consequences of these physiologic and anatomical changes remain largely unknown ( Roberts et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%